Avaliação química e estrutural da semente de moringa - Gallão, Maria Izabel (2022)
Moringa (Moringa oleifera Lam.) is a plant that has been used instead of aluminum salts in water treatment. The aim of this work was to determine the composition and the morphology of the moringa seeds. Cotyledons contain a great amount of proteic bodies. This material was observed with Xylidine Ponceau pH 2.5 stain. Anionic material and starch in the cotyledon cells were not detected by Toluidine blue and PAS reaction stains, indicating that the main reserve material is protein. Empty spaces, which did not reacted with any stain, were observed in the cytoplasm cells from the cotyledon. Such results indicate that these spaces were occupied by lipids, since chemical analysis revealed a great lipid content in the seeds.